Audit Delay Ditinjau Dari Ukuran Perusahaan, Profitabilitas, Solvabilitas Dan Komite Audit - Friska Yuliana (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to determine the influence of company size, profitability, solvency and audit Committee on the audit delay. A research sample is a food and Baverage manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The research sampling was done by purposive sampling method and resulted in a total of 22 companies. The data source is the secondary data of the website (www.idx.co.id). Data is tested with multiple linear regression analyses with the help of SPSS version 21. The test results that the audit committee influence on the audit delay. Meanwhile, company size, profitability and solvency have no effect on the audit delay. The result of this research is expected to be an additional consideration to decide the process of audit delay. And can be additional information users of financial statements for the consideration of investment decisions. Keywords: Audit delay, audit committee, profitability, solvency, company size